Health state utility values for diabetic retinopathy: protocol for a systematic review and meta-analysis - Sampson, Christopher James; Tosh, Jonathan C.; Cheyne, Christopher P.; Broadbent, Deborah; James, Marilyn (BioMed Central, 2015)
Background People with diabetic retinopathy tend to have lower levels of health-related quality of life than individuals with no retinopathy. Strategies for screening and treatment have been shown to be cost-effective. In order to reduce the bias in cost-effectiveness estimates, systematic reviews of health state utility values (HSUVs) are crucial for health technology assessment and the development of decision analytic models. A review and synthesis of HSUVs for the different stages of disease progression in diabetic retinopathy has not previously been conducted.